Surgical trends for benign ovarian tumors among hospitals of different accreditation levels: An 11-year nationwide population-based descriptive study in Taiwan - Ming-Ping Wu; Chia-Jen Wu; Cheng-Yu Long; Chung-Han Ho; Kuan-Hui Huang; Chin-Chen Chu; Cheng-Yang Chou (Elsevier, 2013)
Objective: Using a population-based nationwide database, we describe the changing surgical trends for laparoscopy or laparotomy for benign ovarian tumors among hospitals of different accreditation levels in Taiwan (medical centers, regional hospitals, and local hospitals). Materials and methods: Women who had National Health Insurance and received either laparoscopy or laparotomy as the primary surgery for benign ovarian tumors in Taiwan during 1999-2009 were identified for analysis. Results: In total, 135,793 women who received either laparotomic (39,779) or laparoscopic surgery (96,014) for benign ovarian pathology were identified. The increase in annual laparoscopy number from 7176 in 1999 to 11,046 in 2009 was significant according to a log-linear regression test (p < 0.0001). The decrease in laparotomies from 3845 to 3567 was not significant (p = 0.190). Service volume shifts from local hospitals to regional hospitals were noted, with a concomitant decrease in the numbers of local hospitals. Laparoscopy was used more often than laparotomy among all three hospital accreditation levels. An increasing trend for choosing laparoscopy was observed for medical centers and local hospitals (p < 0.0001), but not regional hospitals (p = 0.0745). Laparoscopy was used more often in younger patients, by younger surgeons, and by male surgeons among hospitals at all three accreditation levels. Conclusion: Laparoscopy was preferentially used over laparotomy at all three hospital levels. An increasing trend for choosing laparoscopy was observed for medical centers and local hospitals, but not regional hospitals. Service volume shifts from local hospitals to regional hospitals were noted. Use of laparoscopy differed according to patient age, surgeon age, and surgeon gender among different hospital levels.